Brief Report: Treatment of Tumor Necrosis Factor–Transgenic Mice With Anti–Tumor Necrosis Factor Restores Lymphatic Contractions, Repairs Lymphatic Vessels, and May Increase Monocyte/Macrophage Egress. Issue 6 (4th April 2017) - Bouta, Echoe M.; Kuzin, Igor; de Mesy Bentley, Karen; Wood, Ronald W.; Rahimi, Homaira; Ji, Rui‐Cheng; Ritchlin, Christopher T.; Bottaro, Andrea; Xing, Lianping; Schwarz, Edward M.
Abstract : Objective: Recent studies have demonstrated that there is an inverse relationship between lymphatic egress and inflammatory arthritis in affected joints. As a model, tumor necrosis factor (TNF)–transgenic mice develop advanced arthritis following draining lymph node (LN) collapse, and loss of lymphatic contractions downstream of inflamed joints. It is unknown if these lymphatic deficits are reversible. This study was undertaken to test the hypothesis that anti‐TNF therapy reduces advanced erosive inflammatory arthritis, associated with restoration of lymphatic contractions, repair of damaged lymphatic vessels, and evidence of increased monocyte egress. Methods: TNF‐transgenic mice with advanced arthritis and collapsed popliteal LNs were treated with anti‐TNF monoclonal antibody (10 mg/kg weekly) or placebo for 6 weeks, and effects on knee synovitis, lymphatic vessel ultrastructure and function, and popliteal LN cellularity were assessed by ultrasound, histology, transmission electron microscopy (TEM), near‐infrared indocyanine green imaging, and flow cytometry. Results: Anti‐TNF therapy significantly decreased synovitis (∼5‐fold; P < 0.05 versus placebo), restored lymphatic contractions, and significantly increased the number of popliteal LN monocyte/macrophages (∼2‐fold; P < 0.05 versus placebo). TEM demonstrated large activated macrophages attached to damaged lymphatic endothelium in mice with early arthritis, extensively damaged lymphatic vessels in placebo‐treated mice with advanced arthritis, and rolling leukocytes in repaired lymphatic vessels in mice responsive to anti‐TNF therapy. Conclusion: These findings support the concept that anti‐TNF therapy ameliorates erosive inflammatory arthritis, in part via restoration of lymphatic vessel contractions and potential enhancement of inflammatory cell egress.